AGILE SUPPLY CHAIN MANAGEMENT IN AGRICULTURAL BUSINESS - Syromyatnikov, Denis; Geiko, Alexandr; Kuashbay, Sattar; Sadikbekova, Aizharkyn (International Journal of Supply Chain Management, 2020)
Abstract? The modern development of the agricultural business in the world is focused on a system of flexible network management, innovations, information, and intellectual property. Large companies are of great significance in this process; agricultural holdings are very important in Russian agricultural business. Unfortunately, the Russian agribusiness sector is dominated by small and medium-sized enterprises, namely, concurrent enterprises, farms, small businesses in rural areas. They produce and market agricultural products. Therefore, supply chain management in agricultural business requires digitalization and the use of flexible management methods. The purpose of the research is to study agile supply chain management methods in agricultural business. We have considered such flexible methods as a digital platform and a blockchain technology, which contribute to the partnership between small and medium-sized agrifood enterprises by creating a digital network platform for all parties interested in the agricultural product. These methods are more productive compared to the traditional approaches; they provide more efficient interaction between manufacturers, consumers and intermediaries in the flow of goods and services through the supply chain. Unfortunately, agile supply chain management in the agricultural business of Russia has not been widely introduced yet, which makes it difficult to collect analytical information. We believe that this may be explained by the predominance of small and medium-sized enterprises in the country, the lack of digital platforms that act as intermediaries in the supply chain to connect crop producers and consumers.